2023
DOI: 10.1101/2023.10.16.562633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Restoring AIBP expression in the retina provides neuroprotection in glaucoma

Won-Kyu Ju,
Yonju Ha,
Seunghwan Choi
et al.

Abstract: Glaucoma is a neurodegenerative disease manifested in retinal ganglion cell (RGC) death and irreversible blindness. While lowering intraocular pressure (IOP) is the only proven therapeutic strategy in glaucoma, it is insufficient for preventing disease progression, thus justifying the recent focus on targeting retinal neuroinflammation and preserving RGCs. We have identified apolipoprotein A-I binding protein (AIBP) as the protein regulating several mechanisms of retinal neurodegeneration. AIBP controls excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Of interest, our recent and ongoing studies have revealed that deficiencies of AIBP and ABCA1, crucial regulators of cholesterol metabolism, are notably evident in RGCs and Müller glia endfeet in both glaucomatous human and mouse retinas. These results link to the degeneration of RGCs [12,13]. Importantly, these findings strongly suggest that dysregulation of cholesterol homeostasis plays a critical role in RGC degeneration and glial dysfunction in glaucomatous neuroinflammation and neurodegeneration.…”
Section: Potential Role Of Aibp In Lipid Rafts and Cholesterol Metabo...mentioning
confidence: 65%
See 4 more Smart Citations
“…Of interest, our recent and ongoing studies have revealed that deficiencies of AIBP and ABCA1, crucial regulators of cholesterol metabolism, are notably evident in RGCs and Müller glia endfeet in both glaucomatous human and mouse retinas. These results link to the degeneration of RGCs [12,13]. Importantly, these findings strongly suggest that dysregulation of cholesterol homeostasis plays a critical role in RGC degeneration and glial dysfunction in glaucomatous neuroinflammation and neurodegeneration.…”
Section: Potential Role Of Aibp In Lipid Rafts and Cholesterol Metabo...mentioning
confidence: 65%
“…Conversely, administration of recombinant AIBP prevented Müller glia-mediated inflammatory response and promoted RGC survival in a mouse model of acute IOP elevation. Intriguingly, AIBP protein expression is reduced in glaucomatous human and mouse retinas [12,13]. Based on these results, we propose that restoring AIBP expression in the retina can provide neuroprotection in glaucoma.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations